Does skin in the game help? Bank franchise value, managerial incentives and ‘going for broke’ - Pathan, Md Shams Tabrize; Haq, M.; Williams, B. (SAGE PUBLICATIONS LTD, 2016)
© 2015, © The Author(s) 2015. The roles bank franchise value (‘skin in the game’) and CEO ownership play in determining bank risk are studied for large United States Bank Holding Companies. We find robust evidence of a convex relation between bank risk and each of CEO shareholding and franchise value, indicating that increases in each are initially risk decreasing, but as franchise value and CEO ownership increases so too does bank risk. Further, we find that low levels of franchise value combined with high CEO ownership result in managerial incentives aligning with those of shareholders, resulting in increased bank risk (‘going for broke’ or asset substitution). We argue that these results are consistent with those of Robert Merton, but in the context of franchise value rather than bank capital and deposit insurance, and accordingly offer some policy recommendations for regulatory monitoring of bank risk that are consistent with these results.